Réponses

  • Utilisateur Brainly
2013-08-05T19:54:43+02:00

 a+b)² = a² + 2 ab + b²
(a-b)² = a² - 2ab +b²
(a-b)(a+b) = a² -b²

 


(x²-2)*(x²-2)=x^4-2x²-2x²+4=x^4-4x²+4

A= (x²+2)²=(x²)²+(2)²+ 2.x².2 = x4+ 4 + 4x² = x^4 + 4x² + 4



B= (2x+1)²+(2x-1)²-8x²

=(2x)²+ 12 + 2.2x.1 + (2x)²+ 12 - 2.2x.1 -8x²
= 4x2+1+4x + 4x2+1-4x -8x² 
= 2



C=2(3t-5)²-2(1-4t)²
C=2(9t²-30t+25)-2(1-8t+16t²)
=18t²-60t+50-(2-16t+32t²)
=18t²-60t+50-2+16t-32t²
=-14t²-44t+48



D=(1+4y)²-(2y+3)-(1+4y)(2y+3)

= 1+16y²+8y-2y-3-2y-3-8y²-12y

= 8y²-8y-5